Broccoli microgreens treated with CaCl2 solution absorb calcium atoms and accumulate them as Ca(II) hydrated ions. (September 2022) - Abe, Hitoshi; Oshita, Hiromi
Abstract: Broccoli microgreens treated with 10 mM CaCl2 aqueous solution were investigated to clarify whether they absorb calcium (Ca) atoms and what chemical states absorbed Ca species take. X-ray fluorescence (XRF) measurements using synchrotron radiation were performed to map Ca concentrations in cotyledon (seed leaf) of broccoli microgreens. The mapping pixel size was 20 μ m × 20 μ m. The broccoli microgreens treated with 10 mM CaCl2 aqueous solution show Ca concentrated areas in the cotyledon. On the other hand, no Ca concentrated areas were observed for the cotyledon of the other broccoli microgreens that were treated with purified water. The Ca chemical state of the Ca concentrated areas was studied by x-ray absorption near edge structure (XANES) spectra. The obtained XANES spectrum of the Ca concentrated area shows the characteristic features of CaCl2 aqueous solution, and it does not correspond to the XANES spectrum of CaCl2 powders. Graphical abstract: Image 1 Highlights: Broccoli microgreens treated with 10 mM CaCl2 were studied by Ca XRF and XANES. 2D images of the Ca XRF were mapped with the pixel size of 20 μ m × 20 μ m. The cotyledon of the broccoli microgreens shows Ca concentrated areas. The Ca chemical state of the Ca concentrated areas was investigated by XANES. Ca(II) hydrated ions in the Ca concentrated areas, no solid species precipitated.